Kepemilikan Tanah dalam Konsep Hukum Positif Indoensia, Hukum Adat dan Hukum Islam - Zuman Malaka (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2018)
In this paper will be presented the concept of land ownership, the discussion not only in the perspective of Indonesian positive law, but also in the perspective of Customary Law and Islamic Law. The aim is intended as a legal comparison to broaden the concept of land ownership. Because with the comparison of legal system will be obtained equations and differences, so it can find the best. At the end of this paper, three things are concluded. First, that the concept of land ownership in positive law in Indonesia is (1) the government in various policies seeks to regulate the utilization, appropriation and use of land for the benefit of mankind in Indonesia, and (2) known the concept of ownership there is a communal religious element. Secondly, the concept of land ownership in customary law is: (1) the existence of Ulayat rights, (2) the subject is customary law community, and (3) the object is covering all the land of customary law community. Third, that the concept of land ownership in Islamic law is: (1) everything belongs to Allah SWT. which is empowered to human beings, so as to use the law of God, (2) to apply the property of individuals and the public equally, (3) unknown to the landlord system.